EGR3-HDAC6-IL-27 Axis Mediates Allergic Inflammation and Is Necessary for Tumorigenic Potential of Cancer Cells Enhanced by Allergic Inflammation-Promoted Cellular Interactions - Kwon, Yoojung; Kim, Misun; Kim, Youngmi; Jeong, Myeong Seon; Jung, Hyun Suk; Jeoung, Dooil (Frontiers in Immunology, 2021)
The objective of this study was to investigate mechanisms of allergic inflammation both in vitro and in vivo in details. For this, RNA sequencing was performed. Early growth response 3 gene (Egr3) was one of the most highly upregulated genes in rat basophilic leukemia (RBL2H3) cells stimulated by antigen. The role of Egr3 in allergic inflammation has not been studied extensively. Egr3 was necessary for passive cutaneous anaphylaxis (PCA) and passive systemic anaphylaxis (PSA). Egr3 promoter sequences contained potential binding site for NF-κB p65. NF-κB p65 directly regulated Egr3 expression and mediated allergic inflammation in vitro. Histone deacetylases (HDACs) is known to be involved in allergic airway inflammation. HDAC6 promoter sequences contained potential binding site for EGR3. EGR3 showed binding to promoter sequences of HDAC6. EGR3 was necessary for increased expression of histone deacetylase 6 (HDAC6) in antigen-stimulated RBL2H3 cells. HDAC6 mediated allergic inflammation in vitro and PSA. TargetScan analysis predicted that miR-182-5p was a negative regulator of EGR3. Luciferase activity assay confirmed that miR-182-5p was a direct regulator of EGR3. MiR-182-5p mimic inhibited allergic inflammation both in vitro and in vivo. Cytokine array showed that HDAC6 was necessary for increased interleukin-27 (IL-27) expression in BALB/C mouse model of PSA. Antigen stimulation did not affect expression of EBI3, another subunit of IL-27 in RBL2H3 cells or BALB/C mouse model of PCA or PSA. IL-27 receptor alpha was shown to be able to bind to HDAC6. IL-27 p28 mediated allergic inflammation in vitro, PCA, and PSA. Mouse recombinant IL-27 protein promoted features of allergic inflammation in an antigen-independent manner. HDAC6 was necessary for tumorigenic and metastatic potential enhanced by PSA. PSA enhanced the metastatic potential of mouse melanoma B16F1 cells in an IL-27-dependent manner. Experiments employing culture medium and mouse recombinant IL-27 protein showed that IL-27 mediated and promoted cellular interactions involving B16F1 cells, lung macrophages, and mast cells during allergic inflammation. IL-27 was present in exosomes of antigen-stimulated RBL2H3 cells. Exosomes from antigen-stimulated RBL2H3 cells enhanced invasion of B16F1 melanoma cells in an IL-27-dependemt manner. These results present evidence that EGR3-HDAC6-IL-27 axis can regulate allergic inflammation by mediating cellular interactions.